Effect of cultivation conditions on the activity of the beromycin producer Streptomyces glomeratus 3980 and its spontaneous variants - Blumauerová, M; Podojil, M; Gauze, G F; Maksimova, T S; Panos, J; Vanĕk, Z (Folia microbiologica, 1980)
Optimal conditions for the submerged cultivation of Streptomyces glomeratus 3980, producer of the anthracycline antibiotics beromycins, and its variants were sought in media with glucose, soybean meal and salts differing in the content of ammonium sulphate. As compared with the original activity of the strain the antibiotic titre of some variants increased about 12 times on increasing the glucose concenration from 3 to 5%, or on omitting CaCO3 from the medium (i.e. under conditions leading to an increased production of propionic acid and suppression of production of the melanin-like pigment). In melanin-less variants accumulating propionate even under standard conditions the activity increased about 18-40 times in the medium with 3% glucose and 0.2% CaCO3 under conditions of more intensive aeration (i.e. under conditions when no propionic acid accumulated). Individual strains also differed in the requirement for (NH4)2SO4 in the medium, their response to changes of volume of the vegetative inoculum and semsitivity to MgSO4 x 7H2O. The biosynthetic activity of all strains was inhibited by the addition of ZnSO4 x 7H2O or CaCl2 and substitution of glucose with starch, lactose or sucrose.
Keywords: Culture Media; Genetic Variation; Ammonium Sulfate; Calcium Carbonate; Magnesium Sulfate; kultivační média; genetická variace; uhličitan vápenatý; glukosa; síran amonný; Streptomyces; Antibiotics, Antineoplastic; Glucose; protinádorová antibiotika; síran hořečnatý